Propensity score analysis of endoscopic and open approaches to malignant paranasal and anterior skull base tumor outcomes. (12th March 2016) - Farquhar, Douglas; Kim, Luke; Worrall, Douglas; Chiu, Alexander; Lee, John Y. K.; Khalili, Sammy; Grady, Sean; O'Malley, Bert W.; Kennedy, David W.; Newman, Jason G.; Palmer, James N.; Adappa, Nithin D.
Abstract : Objectives/Hypothesis: Malignant sinonasal and skull base tumors are now being resected using an endoscopic technique, but there has been controversy regarding the oncologic safety of this approach. Various studies have compared the outcomes from endoscopic surgery to those from open techniques; however, all have been limited by substantial differences in the patient populations receiving each approach. In this study we compare outcomes of open and endoscopic techniques and use propensity score matching to control for these differences in the patient populations. Study Design: Retrospective cohort study including all patients > 18 years old receiving primary surgery for malignant sinonasal or skull base tumors at our institution from 2002 to 2013. Results: One hundred twenty‐four patients met criteria; 82 received endoscopic‐only surgery, and 42 had an open component to their approach. There was an 86% 3‐year overall survival and a 74% disease‐free survival. Without controlling for differences in the groups, the endoscopic patients fared significantly better in survival, recurrence rates, wound infections, and length of hospital stay. When using propensity score matching to account for patient comorbidities and tumor size, there were no significant differences in any outcomes except length of the hospital stay. A multivariate regression analysis yielded the same results. Conclusion: In this study, endoscopic surgery was shown to be a safe alternative to the open technique, even when controlling for the favorable patient and tumor characteristics in endoscopic patients. This is the first study to account for these differences with a rigorous statistical methodology. Level of Evidence: 4. Laryngoscope, 126:1724–1729, 2016